Implementation of six patient safety goals at a public health centre with in-patient services in Bali, Indonesia: A qualitative case study - Gunawan, I Made Abdi; Wirawan, I Made Ady; Lubis, Dinar Saurmauli (Universitas Udayana, 2021)
Background and purpose: The Indonesian government requires all health care facilities including public health centres (PHCs) to implement a patient safety program as part of the accreditation standard process. The implementation of patient safety in PHCs have faced various problems, including human resources and infrastructure issues. This study aims to explore the implementation of patient safety target procedures in an accredited inpatient PHC in Tabanan District, Bali, Indonesia.Methods: We conducted a qualitative case study that adopts four main domains in patient safety, consisting of executive officers, community or patient who received services, systems in service delivery and methods, and elements in each domain. The research location was at Penebel I PHC, an inpatient PHC with the accreditation status of “utama”. Data collection was carried out from March to April 2020. It includes observation of the patient safety implementation, review on tracking patient safety documents and in-depth interviews with 11 informants who are PHC staff, patients’ safety task force and the family of patients. The data were analysed using thematic analysis by creating a grid of themes, sub-themes and data reduction to narrative presentation. Results:The patient safety procedure in Penebel I PHC has been carried out through the standard and procedure according to the Ministry of Health (MoH) regulation which consist of patient identification; communication between staff and patients; maintain the safety of High Alert and Look Alike Sound Alike (LASA) medications. However, there is a need to improve the capacity of implementing officers to increase their communication competencies as well as to enhance cooperation between officers in health services to avoid patient safety incidents. Conclusion:The implementation of six patient safety goals in-corporate through four main domains of health care services has been running according to the MoH’s standard. There is a need to improve the competence of officers, cooperation between officers in carrying out patient safety management and improve communication between officers and patients so that the information conveyed by officers is truly understood by patients.